Effect of myofascial release techniques on internal biomechanics and their resultant application to sports: A systematic review - Duarte Franca M.E.* (2024)
© 2024 Elsevier LtdObjective: To investigate the influence of myofascial release (MFR) techniques on biomechanical parameters, including force, speed, Range of Motion (ROM), and flexibility in athletes. Method: This is a systematic review conducted on the databases United States National Library of Medicine (PubMed), Scopus, Scientific Electronic Library Online (SciELO); LILACS, and Embase. The PRISMA guidelines – 2020 were followed, and bias risk analysis was performed using the Cochrane Handbook tool (RoB2). Results: Sixteen studies were included for qualitative analysis. Techniques using MFR applied or self-applied to improve strength, speed, ROM and flexibility, have no consensus regarding the period of their applicability, due to difficulties in identifying the ideal load of applied tension, temperature level, and viscoelastic properties during the release of the deep fascia. However, improvements in oxygenation, reorganization of piezoelectricity, and normalization of fascial tension became evident after MFR. Conclusion: Regarding strength, speed, and range of motion (ROM), instrument-assisted soft tissue mobilization performed in isolation and self-applied techniques combined with other methods emerged as favorable predictors for lower limb outcomes. However, isolated self-myofascial release requires further investigation. Regarding flexibility, there is a contrast in results between the use of self-applied foam rolling in isolation, which seems to prevent densification but suggests improvements in muscle strength acquisition without compromising flexibility. Applied MRF provided a more flexible quality for scapular mobilization, both in isolation and in combination with other techniques, but its best indication and/or specific applicability is for pain reduction.